The Perception of Mustafa Kemal Pasha-Enver Pasha Conflict in the French Public Opinion during the National Struggle Period - Mustafa Kırışman (Yakın Dönem Türkiye Araştırmaları)
Enver Pasha was a critical figure who had a say in the fate of the country by simultaneously assuming the duties of the Chief of Military Affairs, Minister of War and Deputy Commander-in-Chief in the Ottoman Empire during the First World War. As the Ottoman Empire was on the defeated side at the end of the war, Enver Pasha and his entourage left the country on November 1, 1918. Mustafa Kemal Pasha, who set foot in Samsun on May 19, 1919, initiated the period of congresses in Anatolia and The National Struggle Movement emerged at the end of this process. The years 1920-1921 coincided with the period when the critical phases of the National Struggle occurred, France was the occupier in Antep and its surroundings, and Enver Pasha was in search of a new struggle. Enver Pasha’s activities abroad and his idea of moving to Anatolia caused tension between him and Mustafa Kemal Pasha. The French, on the one hand, tried to understand the level of the relationship between Mustafa Kemal Pasha and Enver Pasha and whether they acted together or not. France, as an occupying country in Antep and its surroundings, needed to develop a new policy on Türkiye. This study tries to reveal how the French public understood the relationship between Mustafa Kemal Pasha and Enver Pasha.